Pseudobactrodesmium (Dactylosporaceae, Eurotiomycetes, Fungi) a Novel Lignicolous Genus - Dong, Wei; Hyde, Kevin D.; Doilom, Mingkwan; Yu, Xian-Dong; Bhat, D. Jayarama; Jeewon, Rajesh; Boonmee, Saranyaphat; Wang, Gen-Nuo; Nalumpang, Sarunya; Zhang, Huang (Frontiers in Microbiology, 2020)
During our ongoing surveys of fungi on submerged wood in the Greater Mekong Subregion, we collected two new species similar to Bactrodesmium longisporum. Pseudobactrodesmium is introduced to accommodate the new species and P. longisporum is transferred to this genus. Fasciculate conidiophores, enteroblastic conidiogenous cells and subulate or fusiform, phragmoseptate conidia with a tapering apical cell and sheath characterizes the genus. Pseudobactrodesmium aquaticum has longer conidia than P. chiangmaiensis. The placement of Pseudobactrodesmium in Dactylosporaceae (Eurotiomycetes) is a novel finding based on analyses of combined LSU, SSU, ITS and RPB2 sequence data. Species named Bactrodesmium longisporum in GenBank appear to represent other unnamed species, indicating that Pseudobactrodesmium is likely to be a speciose genus with different species in streams around the world.